Optimalisasi Digital Marketing di Marketplace - Alfina Maulida; Dwimei Ayudewandari Pranatami (Universitas Kristen Indonesia Toraja, 2024)
This Real Work Lecture (KKN) program aims to improve the digital marketing skills of MSME players in Sekaran Village, Gunungpati District, Semarang City. With technological developments, digital marketing has become important to expand market reach and increase sales. This activity includes training and seminars on the basics of digital marketing, choosing the right marketplace, optimizing seller accounts, as well as implementing SEO and decorating online stores. Participants are also invited to practice directly creating an account, uploading products, and optimizing their shop. The results of the activity showed an increase in participants' knowledge and skills in digital marketing, as well as an increase in traffic and sales on their marketplace accounts. This program has succeeded in having a positive impact on MSMEs, helping them utilize technology to achieve greater business success